1999
DOI: 10.1292/jvms.61.531
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization and Cortical Granule Distribution of Bovine Oocytes Having Heterogeneous Ooplasm with Dark Clusters.

Abstract: ABSTRACT. In vitro maturation, fertilization and subsequent development of oocytes with homogeneous (category 1), or heterogeneous ooplasm (category 2) were investigated. No significant differences were observed in the nuclear maturation and total fertilization rates between the two categories. However, category 2 oocytes showed a higher normal fertilization rate due to their lower incidence of polyspermy as compared to category 1 oocytes. Electron microscopic study revealed that all category 2 oocytes had cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The changes in percentage of dark clusters in the ooplasm apparently involve the rearrangement of vesicles and lipid droplets from an even distribution to a more polarized appearance in mares [16]. The positive association between the percentage of ooplasm with dark granules and the oocyte maturation rate in the present in vivo study with equine oocytes is consistent with an in vitro study in cattle that indicated that oocytes with dark clusters of granules had a higher potential for maturation [31]. a Within oocyte recovery groups and within oocyte maturity groups, means are significantly different or approach being significantly different as follows: *** P , 0.001; ** P , 0.01; * P , 0.05; # P , 0.1.…”
Section: Discussionsupporting
confidence: 89%
“…The changes in percentage of dark clusters in the ooplasm apparently involve the rearrangement of vesicles and lipid droplets from an even distribution to a more polarized appearance in mares [16]. The positive association between the percentage of ooplasm with dark granules and the oocyte maturation rate in the present in vivo study with equine oocytes is consistent with an in vitro study in cattle that indicated that oocytes with dark clusters of granules had a higher potential for maturation [31]. a Within oocyte recovery groups and within oocyte maturity groups, means are significantly different or approach being significantly different as follows: *** P , 0.001; ** P , 0.01; * P , 0.05; # P , 0.1.…”
Section: Discussionsupporting
confidence: 89%
“…The better developmental competence achieved by oocytes, and consequently increases in blastocyst formation, after exposure to 5 nm RA during IVM could be related to more complete granular migration in the matured oocyte cytoplasm induced by RA, as suggested to occur in bovine oocytes . This migration provides a block to polyspermy once migrated cortical granules (CGs) have been released (Wang et al 1997b;Nagano et al 1999). It is well known that CGs play an important role in the block to polyspermy in mammalian oocytes (for a review, see Yanagimachi 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine ovaries obtained at a local abattoir were kept in normal saline at 25–30 °C and delivered to the laboratory within 6 h of their collection. Cumulus–oocyte complexes (COCs) were collected from small antral follicles (2–8 mm in diameter) by aspiration as des-cribed previously (Nagano et al ., 1999). All COCs were washed twice in HEPES-buffered Tyrode's medium (TALP–HEPES) (Bavister et al ., 1983) supplemented with 3 mg/ml of bovine serum albumin (BSA, fraction V, Sigma), 0.2 mM sodium pyruvate and 50 μg/ml of gentamicin sulfate (Sigma).…”
Section: Methodsmentioning
confidence: 99%